POLA KONSUMSI SARAPAN PAGI MURID SEKOLAH DASAR DI SDN 060921 KECAMATAN MEDAN SUNGGAL TAHUN 2015 - Ratna Juwita Sari; Zulhaida Lubis; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Breakfast is important activity to start activity every morning and purpose to increase of learning concentration and physical ability of school children. This purpose of study was to know model of breakfast consumption of students in SDN 060921 Kecamatan Medan Sunggal year 2015. This study is a survey research with cross sectional approach. This study population is all grades 5 and 6 of the academic year 2014/2015 SDN 060921 Kecamatan Medan Sunggal. Sampling tecnique used was total sampling with a sample obtained as many as 74 people. Means of collecting data used are questionnaires. The study conducted in April until July 2015. The result of the study showed that students of SDN 060921 Kecamatan Medan Sunggal have frequency of breakfast everyday (41.9%), students eat rice and chicken for breakfast (20.3%) and students drink tea for breakfast (50%). Most of students have breakfast contribution of adequate nutrition energy (59.5%), protein (59.5%) and vitamin A (55.4) with enough categories. Meanwhile contribution of vitamin C (75.7%), iron (62.2%) and calcium (85.1%) most of students have adequate nutrition with less categories. Breakfast models students based on frequency was good, but adequate nutrition breakfast of most student not quite good. Recommended for principal increase knowledge about breakfast and students parent help breakfast habits everyday with selection menu and nutrition value of breakfast based on needed. Keywords : models of breakfast consumption, students